Comparative analysis of the social component when assigning an ESG rating - R. S. Golovnin; T. V. Baibakova (Вестник университета)
Every year, Russian companies are using ESG (environmental, social, governance) ratings more actively as a  tool to   increase their investment attractiveness. At   the same time, there are no   clear standards in   the world and domestic practice that should be   considered when forming these ratings. In   this regard, the ESG methodologies presented on   the Russian market are based on  extremely subjective criteria and approaches to  their assessment. This can lead to   dramatically different results of   the ESG ratings from different  analytical agencies. In   order to  verify this fact, the authors of   the article have conducted a   study the essence of  which is  to calculate and further compare the S-criterion based on   the methodologies of   several large Russian analytical agencies providing ESG assessment services. This approach has allowed us   to assess in   practice the degree of   differences that underlie the formation of   the ESG methodologies. The result of   the work is   that the results of  the S-components of   the domestic ESG agencies are highly similar, which has not confirmed the hypothesis made by  the authors. Despite the fact that each of   the ESG methodologies ha   included different, often dissimilar indicators, the result of  the study has revealed their remarkable efficiency and consistency with each other. Contrary to   the concerns of  regulators and researchers, the results of  the agency ratings show a  high degree of   mutual similarity. Further research should be   aimed at  evaluating the E   and G   components of  the ESG ratings of  the Russian analytical agencies, and at   summarising the findings obtained for the final refutation or  acceptance of   the made hypothesis.